Association of genetic markers of PLEKHA7, ABCC5 and KALRN and progression of primary angle closure glaucoma in Malay patients - Thangavelu, Lathalakshmi (2017)
INTRODUCTION Glaucoma is the leading cause of irreversible blindness worldwide, with Asians accounting for approximately half of the world’s glaucoma cases. Primary angle closure glaucoma (PACG) is highly prevalence among Asians. The prevalence of PACG varies widely according to the different races in Asia. PACG prevalence in Malays ranges from 0.12% to 2.5%. Asians patients with PACG are found to progress faster than Caucasians. PACG is responsible for more blindness in Asian population. Identifying the potential susceptible genetic markers for progression of PACG in Malays is essential for management strategy to prevent blindness and future development of new treatment. OBJECTIVE To determine association of genetic markers of PLEKHA7, ABCC5 and KALRN and progression in PACG Malay patients. METHODOLOGY A cross sectional study was conducted between April 2015 and April 2017 involving Malay patients with PACG from Hospital Universiti Sains Malaysia and Hospital Raja Perempuan Zainab II (Kota Bharu). Venesection was performed. DNA extraction was conducted using commercialize DNA extraction kit (QIAGEN, Germany). Optimization of primer was conducted for rs11024102 of PLEKHA7, rs17217796 of ABCC5 and rs1392912 of KALRN. Polymerase chain reaction (PCR) was carried outusing Thermocycler SureCycler 8800 (Agilent Technologies, Santa Clara, CA). PCR products were purified using Illustra Exostar (Ge Healthcare Bio-Science) PCR product purification kit. PCR products were sent to a private laboratory (First Base laboratories, Selangor, Malaysia) for cycle sequencing. Humphrey visual fields (HVF) were conducted during study recruitment. HVF obtained were compared with two baseline visual field. Patients were grouped into progress and non-progress based on the agreement of both AGIS and Hodapp-Parrish scoring system on HVF. Chi Square test was used to analyse association of genetic markers and progression of PACG. RESULTS A total of 163 Malay patients were recruited with PACG primary (58 men and 105 women). Forty nine or approximately 30% of patients had acute primary angle closure attack. There were 29 (18%) patients with visual field progression of PACG after a mean follow up of 6.0 (SD 1.0) years. Minor allele frequency (MAF) for PLEKHA7 rs11024102 (G/A), ABCC5 rs17217796 (C/G) and KALRN rs1392912 (A/G) is 0.44, 0.08 and 0.48 respectively. There was no statistically significant association between rs11024102 (p=0.828), rs17217796 (p=0.865) and rs1392912 (p=0.684) with progression of PACG in Malay patients.CONCLUSION Although genetic markers of PLEKHA7 and ABCC5 were found to associate with the risk of PACG but they have no role on progression of PACG in Malay population. In this study, KALRN gene did not show any role on progression of PACG in Malay population. Perhaps, there are other susceptible genetic markers responsible for progression in PACG.